(untitled) (REMUNOM, 2025)
Digital technologies transform everyday reality and are becoming increasingly present in society. In this context, through a literature review, this study aims to analyze the impact of digital technologies on education, with an emphasis on accessibility issues and the use of digital tools, particularly in distance education environments. From the perspective that learning occurs through mediation between teachers and students, based on culture and each individual’s experiences, this study considers how digital technologies contribute to knowledge construction and promote the inclusion of people with Special Educational Needs (SEN). Grounded in the socio-interactionist perspective proposed by Vygotsky, the analysis includes a survey of educational technologies for accessibility, the preparation of teachers and students, and proposes practices to make digital environments more accessible and welcoming for all. Keywords: Accessibility. Education. Digital inclusion. Inclusive education. Inclusion in distance education.